Clinical response to nonsurgical periodontal therapy is associated with decreased serum leukocyte count and uric acid levels in kidney transplant recipients - Samira Vasconcelos Gomes; Danila Lorena Nunes-; Luciana Salles Branco-; Bruno Braga Benatti; Vandilson Rodrigues (University of São Paulo, 2024)
Abstract Objective: This study sought to investigate the relationship between clinical response to nonsurgical periodontal therapy (NSPT) and serum changes in leukocyte count, fasting blood glucose, hemoglobin, hematocrit, creatinine, and uric acid in kidney transplant recipients (KTR). Methodology: A prospective study was performed on 20 KTRs. Periodontal and serum data were collected before and 90 days after NSPT, and delta values (Δ = after NSPT - before) were calculated. Periodontal assessment included periodontal probing depth (PPD), clinical attachment level (CAL), and bleeding on probing (BOP). Patients were classified based on the presence of periodontitis and then categorized into stages. Results: Patients showed a reduction in the percentage of sites with PPD≥3mm, PPD≥4 mm and BOP, after NSPT. There was a direct correlation between the deltas of leukocyte count and CAL ≥3 mm (r=0.645, P=0.002) and BOP (r=0.663, P=0.001), and the deltas of uric acid and CAL ≥3 mm (r=0.562, P=0.010). Conclusion: A good clinical response to NSPT may affect the reduction of serum levels of leukocyte count and uric acid, suggesting a beneficial effect on systemic health in KTR.